Magnesium Impurities Decide the Structure of Calcium Carbonate Hemihydrate - Aufort, Julie; Demichelis, Raffaella (AMER CHEMICAL SOC, 2020)
The new and recently detected hydromorph of calcium carbonate, CaCO3·12H2O hemihydrate, has been analyzed via both first-principles and classical theoretical methods. The orientation of the water molecules, that remained unclear in the experiment, has been determined. A structure with symmetry higher than that originally proposed results from geometry optimization (Pbcn, space group number 60) of the pure phase. The introduction of magnesium impurities causes a distortion in the unit cell, which assumes the monoclinic arrangement (P21/c) originally proposed. This is consistent with the magnesium-rich experimental conditions.